Vasculitis in children with acute urticaria - Tunçer, Ayfer; Saraçlar, Yıldız; Tuncer, İlhan; Adalıoğlu, Gönül (The Turkish Journal of Pediatrics, 1983)
Circulating immune complexes and vasculitis in patients with acute urticaria have been investigated in this study. Twelve of the 20 patients with acute urticaria had circulating immune complexes (60%). Vasculitis was found to be present in 5 patients (25%).
Keywords: childhood acute urticaria; immune complex; vasculitis